Rendahnya Implementasi Nilai-Nilai Pancasila pada Peserta Didik Di Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine the implementation of Pancasila values in elementary schools based on previous articles. The research method uses a qualitative research approach or descriptive approach, and the basis for the discussion is obtained from the results of literature searches for existing sources of books, journals and relevant articles. These findings highlight the factors that influence the poor implementation of Pancasila values in elementary schools. Efforts to overcome this include making improvements by revising the curriculum, developing teaching methods, improving teacher role models, and providing adequate facilities so as to increase awareness of Pancasila values among students. It is hoped that internalization can be encouraged and students will increasingly develop into individuals with character and integrity in the spirit of Pancasila.